Solid pseudopapillary tumor of the pancreas: Frantz´s tumor - Barreda Bolaños, Fernando (2018)
The solid pseudopapillary tumor of the pancreas, also known as Frantz's tumor, is a very rare disease in our country, comprising less than 3 % of pancreatic tumors. Its etiology is unknown and it is predominantly found in young women in their third decade of life. We present the case of a 23-year-old woman who was admitted due to a 3-month burning epigastralgia and early satiety. On examination, she had pain with deep palpation. Her biochemical profile, liver profile, and tumor markers were within normal values. An abdomen and pelvis multislice helical/spiral computed tomography (CT) scan showed a solid cystic neoformative lesion with rounded structure and well-defined borders. Pathology confirmed a solid pseudopapillary tumor of the pancreas. The patient underwent a tumor resection with favorable evolution.